2016
DOI: 10.18632/oncotarget.7564
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 9 regulates breast cancer cell proliferation and the response to histone deacetylase inhibitors

Abstract: Histone lysine acetylation is an epigenetic mark regulated by histone acetyltransferases and histone deacetylases (HDAC) which plays an important role in tumorigenesis. In this study, we observed a strong overexpression of class IIa HDAC9, at the mRNA and protein levels, in the most aggressive human breast cancer cell lines (i.e. in basal breast cancer cells vs luminal ones or in malignant vs begnin MCF10A breast epithelial cell lines). HDAC9 overexpression was associated with higher rates of gene transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
(63 reference statements)
3
40
0
Order By: Relevance
“…A). Finally, GSEA of microarray data obtained from an independent pool of MCF7 cell clones that overexpress or not HDAC9 (Lapierre et al ., ) confirmed that HDAC9 overexpression led to a significant decrease of genes belonging to the ERα signaling pathway (Fig. B).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…A). Finally, GSEA of microarray data obtained from an independent pool of MCF7 cell clones that overexpress or not HDAC9 (Lapierre et al ., ) confirmed that HDAC9 overexpression led to a significant decrease of genes belonging to the ERα signaling pathway (Fig. B).…”
Section: Resultssupporting
confidence: 72%
“…We previously reported that HDAC9 expression was significantly lower in ERα‐positive breast cancer cell lines, such as MCF7 and T47D, compared with ERα‐negative breast cancer cell lines, such as MDA‐MB231 and MDA‐MB436 (Fig. E) (Lapierre et al ., ). Interestingly, the same inverse correlation was found by analyzing several human breast tumor datasets, including the E‐TABM‐158 breast cancer dataset (Chin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…HDAC9 is thought to regulate gene expression through epigenetic modulation of the chromatin structure by catalyzing the deacetylation of histone proteins [19]. More recently, aberrant HDAC9 expression has been observed in several types of cancers, including medulloblastoma [21], acute lymphoblastic leukemia [22], glioblastoma [23], osteosarcoma [24], and breast cancer [25]. HDAC9 has been shown to promote the growth of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC9 is also known to target non-histone proteins, such as forkhead box protein 3, ataxia telangiectasia group D-complementing protein (ATDC), and glioblastoma 1 protein, which are members of pathways implicated in carcinogenesis [20, 21]. More recently, aberrant HDAC9 expression has been observed in several types of cancers, including medulloblastoma [21], acute lymphoblastic leukemia [22], glioblastoma [23], osteosarcoma [24], and breast cancer [25]. HDAC9 has been shown to promote the growth of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear which isoforms are important to target for efficacy in breast cancer. Correlational studies between individual isoform expression and disease state in breast cancer have been disparate (Lapierre et al, 2016, Zhang et al, 2005b, Muller et al, 2013, Hsieh et al, 2016). In addition to expression, HDAC activity can be regulated through formation of multi-protein complexes and PTM (Zhang et al, 1999, Guenther et al, 2000, Zhang et al, 2005a, Pflum et al, 2001).…”
Section: Introductionmentioning
confidence: 99%